#ReadyToPlay: Risk factors in the Norwegian Women's Premier League football - perceptions and priorities of club stakeholders - Kåshagen, I. G.; Amundsen, R.; Moksnes, H.; Møller, M.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2025)
Women's premier league footballers have a high risk of injury. Risk management has been proposed as a framework for improving athlete health, through describing, assessing, and addressing potential risks. This article aim to describe the risks and risk factors for injury and illness that stakeholders in women's football perceive as important, their priorities and how they plan to address them. All key stakeholders in the 11 teams playing in the Norwegian women's premier league participated. They created a tailored risk management plan targeting the 2024 season, describing potential risks for injury and illness and their risk factors, as well as seasonal risks related to their training and match calendar. The risks were assessed individually, and a plan with preventive measures was created to address the prioritized risks. The teams identified 104 risks (49% team, 51% seasonal). Most risks were categorized as Training & match load (42) and Musculoskeletal (42). For these, 248 risk factors were identified; most were categorized as Training & match load (66), Staff & player-related (55), Social/behavioral (52) and Equipment & facilities (47). Of the 104 risks, 61 were prioritized, and 231 preventive measures were planned to address them. The physiotherapist was responsible for 55% of these measures, while the remaining 45% were assigned to other team stakeholders. This study highlights the diversity of risks, risk factors, and planned preventive measures for injury and illness in Norwegian elite women's football. Addressing these issues requires a broad focus beyond physical factors and adopting a holistic approach involving all relevant team representatives.